Sevoflurane attenuates systemic inflammation compared with propofol, but does not modulate neuro-inflammation: A laboratory rat study. Issue 11 (November 2017) - Beck-Schimmer, Beatrice; Baumann, Lukas; Restin, Tanja; Eugster, Philipp; Hasler, Melanie; Booy, Christa; Schläpfer, Martin
Abstract : BACKGROUND: Septic encephalopathy is believed to be a result of neuro-inflammation possibly triggered by endotoxins, such as lipopolysaccharides (LPS). Modulation of the immune system is a property of volatile anaesthetics. OBJECTIVE: We aimed to investigate the systemic and cerebral inflammatory response in a LPS-induced sepsis model in rats. We compared two different sedation strategies, intravenous propofol and the volatile anaesthetic sevoflurane, with the hypothesis that the latter may attenuate neuro-inflammatory processes. DESIGN: Laboratory rat study. SETTING: Basic research laboratories at the University Hospital Zurich and University Zurich Irchel between August 2014 and June 2016. PATIENTS: A total of 32 adult male Wistar rats. INTERVENTIONS: After tracheotomy and mechanical ventilation, the anaesthetised rats were monitored before sepsis was induced by using intravenous LPS or phosphate-buffered saline as control. Rats were sedated with propofol (10 mg kg −1 h −1 ) or sevoflurane (2 vol%) continuously for 12 h. MAIN OUTCOME MEASURES: Systemic inflammatory markers such as cytokine-induced neutrophil chemo-attractant protein 1, monocyte chemo-tactic protein-1 and IL-6 were determined. The same cytokines were measured in brain tissue. Cellular response in the brain was assessed by defining neutrophil accumulation with myeloperoxidase and also activation of microglia with ionised calcium-binding adaptor molecule-1 and astrocytes with glial fibrillary acidic protein. Finally, brain injury was determined. RESULTS: Animals were haemodynamically stable in both sedation groups treated with LPS. Blood cytokine peak values were lower in the sevoflurane-LPS compared with propofol-LPS animals. In brain tissue of LPS animals, chemoattractant protein-1 was the only significantly increased cytokine ( P = 0.003), however with no significance between propofol and sevoflurane. After LPS challenge, cerebral accumulation of neutrophils was observed. Microglia activation was pronounced in the hippocampus of animals treated with LPS ( P = 0.006). LPS induced prominent astrogliosis ( P < 0.001). There was no significant difference in microglia or astrocyte activation or apoptosis in the brain between sevoflurane and propofol. CONCLUSION: We have shown that systemic attenuation of inflammation by the volatile anaesthetic sevoflurane did not translate into attenuated neuro-inflammation in this LPS-induced inflammation model. TRIAL REGISTRATION: Animal approval No. 134/2014, Veterinäramt Zürich. Abstract : Supplemental Digital Content is available in the text